Pola Rekrutmen Partai Politik di Aceh (Studi Kasus Kota Banda Aceh dan Kota Sabang) - Januar, Eka; Khalil, Zakki Fuad (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2017)
In the legislative elections of 2014 based on the Plenary of the Independent Election Commission of Banda Aceh city, the Nasional Demokrat Party is the winner of the legislative election with 13% of the vote. While the winner of legislative election of Sabang City is the Aceh Party that amounted to seven seats. This research used descriptive qualitative analysis which is directed to describe facts, precise arguments and analyze the occurrence of phenomena that occur. This research was conducted through field study by using interview technique aimed to understand the pattern of recruitment of political parties, the doctrine of political parties, the forms of training on party cadres, party officials and elected legislative members. The conclusions of this study are (1) the pattern of recruitment conducted by political parties have different systems and mechanisms, (2) the doctrin of political parties conducted on elected candidates did not have clear rules and control systems, (3) the form and the training conducted by political parties have no specific formulation to the elected legislative candidates in performing the party functions and as representative of the people.